Revised stratigraphic framework for the lower Anti-Atlas Supergroup based on U–Pb geochronology of magmatic and detrital zircons (Zenaga and Bou Azzer-El Graara inliers, Anti-Atlas Belt, Morocco) - Ait Lahna, Abdelhak; Youbi, Nasrrddine; Tassinari, Colombo Celso Gaeta; Basei, Miguel Angelo Stipp; Ernst, Richard E.; Chaib, Latifa; Barzouk, Abdelhafed; Mata, João; Gärtner, Andreas; Admou, Hassan; Boumehdi, Moulay Ahmed; Söderlund, Ulf; et al. (Journal of African earth sciences (1994), 2020)
U–Pb geochronology of magmatic and detrital zircons (Zenaga and Bou Azzer-El Graara inliers, Anti-Atlas Belt, Morocco) and a reassessment of the published constraints suggest a revised stratigraphic framework for the lower Anti-Atlas Supergroup. Five major unconformity-bounded lithostratigraphic packages are here distinguished: the two lower units of Paleoproterozoic age are named the Tasserda-Taghatine Group (2030–1706 Ma) and the Oumoula (Mimount) Formation (ca. 1745–1650 Ma); the third unit of Paleoproterozoic to Neoproterozoic age (ca. 1650 to >883 Ma) is the Tizi n’Taghatine Group; the fourth and fifth units of Neoproterozoic age are the ca. 883 Ma Tachdamt and the ca. 700 Ma Bleida formations. Implications of this revised stratigraphic framework include: 1) the Tasserda-Taghatine Group might be linked to the post-orogenic collapse after the Eburnean Orogeny; 2) the Tizi n’Taghatine Group might be ca. 1.1 Ga in age based on proposed correlation with the Taoudeni Basin succession in Mauritania; 3) the Bleida Formation likely reflects deposition in the foreland basin at the early stage of the Pan-African Orogeny; 4) the Oumoula (Mimount) Formation, Tizi n’Taghatine Group, and Tachdamt Formation potentially record extensional events within the Nuna/Columbia and Rodinia supercontinents; 5) the provenance of the lower Anti-Atlas Supergroup (based on our new detrital zircon dating) is mainly from the West African craton along with possible contributions from other cratons such as Amazonia and the Sahara Metacraton; 6) the flood basalt sequence of the Tachdamt Formation likely belongs to the ca. 885-883 Ma intraplate Iguerda-Taïfast Large Igneous Province (LIP) event defined by previously dated dykes in the Iguerda and Taïfast inliers; and 7) the 1650 Ma Zenaga LIP can be potentially linked with LIP magmatism in Baltica and Laurentia. •The Taghdout mafic sill of the Ifzwane Suite yielded an age of 1676 ± 37 Ma.•The depositional age of the lower Anti-Atlas Supergroup ranges from 2049 to 700 Ma and the provenance is mainly from the WAC.•A new 5-part lithostratigraphic framework for the Proterozoic lower Anti-Atlas Supergroup of the Anti-Atlas Belt is proposed.•The 1650-1640 Ma Zenaga and 885-883 Ma Iguerda-Taïfast LIPs provide important stratigraphic constraints.•Correlation between the lower Anti-Atlas Supergroup and the Taoudeni Basin succession in Mauritania.